2013
DOI: 10.1155/2013/376375
|View full text |Cite
|
Sign up to set email alerts
|

Using the Fuzzy Linguistic Preference Relation Approach for Assessing the Importance of Risk Factors in a Software Development Project

Abstract: This study employs fuzzy linguistic preference relation (Fuzzy LinPreRa) approach to assess the relative degree of impact of risk factors in software development project for two expert groups working in technology enterprises and software development companies. For the identified risk dimensions, the results show the same rankings for these two groups. “Organization function risk” is considered the most important dimension influencing the software development project performance, with the others, in order, bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Many authors (for example, [96,97]) claim that the most frequent among all the suggested defuzzification methods is the so-called centre of gravity (COG) method, also known as "centroid". It is useful due to its simplicity [98,99] and the reliability of the results [91,92,96,[98][99][100][101]. By using the COG method, the crisp weights of criteria and sub-criteria are calculated as follows [98]:…”
Section: A Brief Explanation Of the Last Five Steps Of Fahpmentioning
confidence: 99%
“…Many authors (for example, [96,97]) claim that the most frequent among all the suggested defuzzification methods is the so-called centre of gravity (COG) method, also known as "centroid". It is useful due to its simplicity [98,99] and the reliability of the results [91,92,96,[98][99][100][101]. By using the COG method, the crisp weights of criteria and sub-criteria are calculated as follows [98]:…”
Section: A Brief Explanation Of the Last Five Steps Of Fahpmentioning
confidence: 99%
“…Step3: Aggregate the judgment matrices. Based on the work of [12], the individual evaluation of m decision makers are aggregated using the average value method described below.…”
Section: Determination Of Criteria Weightmentioning
confidence: 99%
“…The current study adopted the mean method. Accordingly, the internal benchmark values (IB) and external benchmark value (EB) are calculated based on Equation (12) and Equation (13) respectively. , 1, 2, , and 1 1…”
Section: Fuzzy Quantified Swot Frameworkmentioning
confidence: 99%
“…Step 1. Expert follows fuzzy linguistic rule (Table 6) [39,40] to evaluate port's green performance on subcriterion and the evaluation result as̃= ( , , ).…”
Section: Performance Evaluation Of Alternatives With Fuzzy Ahpmentioning
confidence: 99%